Radio Project in the Land of the Midnight Sun - Jo Nelson (Journal of Applied Communications, 1969)
Getting bogged down with the daily routine of broadcasting? Or weary of entertaining foreign visitors? Then go off on a short-term professional foreign visit yourself.